Spontaneous Remission in an Older Patient with Relapsed FLT3 ITD Mutant AML - Vachhani, Pankit; Mendler, Jason H.; Evans, Andrew; Deeb, George; Starostik, Petr; Wallace, Paul K.; Wang, Eunice S. (Case Reports in Hematology, 2016)
Spontaneous remission (SR) of acute myeloid leukemia (AML) is a very rare phenomenon. AML characterized by FLT3 internal tandem duplication (FLT3 ITD) is typically associated with an aggressive clinical course with rapid progression, relapse, and short overall survival in the absence of transplantation. We report here the first case of SR of FLT3 ITD mutant AML in the literature. Our patient was an elderly woman with relapsed NPM1 and FLT3 ITD mutant AML whose disease underwent SR for a brief duration without precipitating cause. We review the potential immune mechanisms underlying SR in AML and discuss the implications for novel immunotherapeutic approaches for FLT3 mutant AML.